Botanical drug preparations for alleviating hair loss in menopausal women: a global ethnopharmacological mini-review - Huang, Zhuo; Zhao, Wen-Jie; Gao, Yong-Jie; Huang, Zhi-Rong; Huang, Qing-Rui; Cai, Sui-Zhen; Bi, Ming-Hui (Frontiers in Pharmacology, 2025)
Menopause is a natural physiological transition affecting over one billion women globally. It often brings distressing symptoms, including hair loss, which impacts up to 52% of postmenopausal women due to estrogen decline, increased androgen sensitivity, and oxidative stress. Conventional treatments like minoxidil provide limited efficacy and may cause side effects, underscoring the need for accessible, culturally attuned alternatives. This mini-review explores ethnopharmacological approaches that empower women through traditional remedies targeting multi-mechanistic pathways, supported by emerging clinical data. We conducted a systematic literature search across databases (PubMed, Scopus, Web of Science), focusing on studies from 2015 to 2025 involving botanical interventions. We prioritized randomized controlled trials in vitro studies, and animal models. Key remedies include saw palmetto (Serenoa repens), which inhibits 5α-reductase to reduce dihydrotestosterone by approximately 30%–40%; rosemary oil (Salvia rosmarinus Spenn.), which promotes scalp microcirculation similar to minoxidil; and ginseng (Panax ginseng C.A.Mey.), which enhances follicle proliferation via ginsenosides. Emerging evidence from 2024 to 2025 reviews highlights multi-target mechanisms in plant extracts, including phytoestrogenic and anti-inflammatory effects. Nutraceuticals have demonstrated improved hair density in menopausal cohorts. These low-cost, community-rooted therapies foster women’s autonomy and cultural resilience. This mini-review is not comprehensive; it highlights key challenges in current research, such as limited menopausal-specific evidence and standardization gaps. It advocates for future priorities like interdisciplinary trials integrating ethnobotany with modern pharmacology to bridge global health disparities. This aligns with the special issue’s vision of empowering women through sustainable, nature-based solutions.